The Effect Of Date Palm Extract (Phoenix dactylifera L.) On Orchid Plantlets (Vanda tricolor Lind) Growth using In Vitro Culture - Resita Nursechan; kamsinah kamsinah; Iman Budisantoso (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Vanda tricolor Lindl. is widespread in Java, Bali, and Sulawesi, V. tricolor on natural habitat became scarce due to forest destruction and natural disasters and human activities. To prevent the extinction it can be done by the propagation of orchids using in vitro culture. The addition of dates extract (Phoenix dactylifera L.) containing carbohydrates to increase growth and differentiation of cells in orchids. This study aimed to determine the effect of date palm extract on the growth of V. tricolor L. plants and determine the best dose of date palm extract on the growth of V. tricolor plantlets. This research was conducted experimentally with a Completely Randomized Design (CRD). The addition of dates on Vaccint & Went / VW media consisting of 6 treatments, that are : 0 g/L, 50 g/L, 100 g/L, 150 g/L, 200 g/L, 250 g/L, each treatment repeated 3 times so there are 18 trial units. The source of the explants used was orchid plantlet (V. tricolor L.). The parameters include the number of roots, root length, number of leaves, plantlet height, and leaf length. The research data has been analyzed using Analysis of variance (ANOVA) with a confidence level of 95% and 99%. The result of this research showed that the addition of date palm extract give a result not significant for the number of leaves, the number of roots, the longest leaf length, the longest root length, the plantlet height of the vanda tricolor orchid in vitro.